5(7x+3y)-4(64x-49y)=

Simple and best practice solution for 5(7x+3y)-4(64x-49y)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(7x+3y)-4(64x-49y)= equation:


Simplifying
5(7x + 3y) + -4(64x + -49y) = 0
(7x * 5 + 3y * 5) + -4(64x + -49y) = 0
(35x + 15y) + -4(64x + -49y) = 0
35x + 15y + (64x * -4 + -49y * -4) = 0
35x + 15y + (-256x + 196y) = 0

Reorder the terms:
35x + -256x + 15y + 196y = 0

Combine like terms: 35x + -256x = -221x
-221x + 15y + 196y = 0

Combine like terms: 15y + 196y = 211y
-221x + 211y = 0

Solving
-221x + 211y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-211y' to each side of the equation.
-221x + 211y + -211y = 0 + -211y

Combine like terms: 211y + -211y = 0
-221x + 0 = 0 + -211y
-221x = 0 + -211y
Remove the zero:
-221x = -211y

Divide each side by '-221'.
x = 0.9547511312y

Simplifying
x = 0.9547511312y

See similar equations:

| h(3)=2(3)+4 | | 4Y-3Z=4 | | 4x-6=9x-10 | | 75-x=159 | | 5X-2Y+X=0 | | (2u-5)(8-u)=0 | | 5(7x+3y)-4(8x^2-7y^2)= | | 2.6x-86=1.5x+2 | | x-12.50+0.1x=0.2 | | 9.8=5x+8.5 | | 6.5x+8-3.5x=5 | | -4y+7=27 | | y^4+2x^2-4xy=-2 | | -5(9a+6)= | | 0.5x+0.1=1.9 | | 2x+15=15x+13 | | 2(x-7.1)=9.4 | | -5=-5+d | | 6x+8.57=3x+14 | | a+18=75 | | 31.82-2y=-4.5+3.92 | | x^2-5x-14=17 | | -9b^2+8b-8=0 | | 3x1/3= | | 4ln(3x-5)3=18 | | -20x+29=20x+29 | | (x-7)(x+2)=17 | | 19x+16=86 | | p-13=31 | | a(x)+b=c | | 7e-4(6+2w)=3(w-8) | | -4(5x-7)+1=20x+29 |

Equations solver categories